2012
DOI: 10.1890/es11-00315.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and hierarchical spatial components of animal occurrence: conserving seasonal habitat for greater sage‐grouse

Abstract: Abstract. Developing strategies for sustainable management of landscapes requires research that bridges regionally important ecological and socioeconomic issues, and that aims to provide solutions to sustainability problems. We integrated Global Positioning Systems (GPS) telemetry and statistical modeling to quantify hierarchical spatial and temporal components of occurrence among greater sage-grouse (Centrocercus urophasianus; n ¼ 87), a species of conservation concern, with the larger goal of developing spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 45 publications
(72 reference statements)
2
35
1
Order By: Relevance
“…For example, predicting a species’ distribution has been used to inform endangered species management and habitat conservation efforts (Dzialak et al, 2013; Dzialak, Olson, Harju, Webb, & Winstead, 2012; Fortin, Courtois, Etcheverry, Dussault, & Gingras, 2008; Richardson, Stirling, & Hik, 2005; Roever, Van Aarde, & Leggett, 2013). As one example, such modeling has been employed to address concerns including the evaluation of conservation networks for African elephants ( Loxodonta africana oxyotis ;(Roever et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, predicting a species’ distribution has been used to inform endangered species management and habitat conservation efforts (Dzialak et al, 2013; Dzialak, Olson, Harju, Webb, & Winstead, 2012; Fortin, Courtois, Etcheverry, Dussault, & Gingras, 2008; Richardson, Stirling, & Hik, 2005; Roever, Van Aarde, & Leggett, 2013). As one example, such modeling has been employed to address concerns including the evaluation of conservation networks for African elephants ( Loxodonta africana oxyotis ;(Roever et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We obtained elevation data from the U.S. Geological Survey (USGS) digital elevation model and used the national hydrography dataset to measure the average distance to perennial water sources as well as the density of water within each buffer [20]. We also included the Normalized Difference Vegetation Index (NDVI), a measure of plant primary productivity which has been used in recent GRSG studies [1, 26, 30].…”
Section: Methodsmentioning
confidence: 99%
“…We also measured the distance to sagebrush for those locations that did not contain sagebrush within their buffers. Particularly in the summer, GRSG use other habitat types within the sagebrush complex [5, 20, 3234] and Dunn and Braun [35] found that managers might use 150–200 m as a guideline for the interspersion of cover types on GRSG summer range. Dunn and Braun [35] reported observations of GRSG feeding on the edges of vegetation cover that was higher in vertical and horizontal structure.…”
Section: Methodsmentioning
confidence: 99%
“…Tack (2009) found negative relationships with more roads around leks at all levels of lek attendance, but impacts were greatest for larger leks (>25 males); the probability of occurrence of a large lek was 50% with road densities of approximately 15.5 miles (25 kilometers) of road within 1.99 miles (3.2 kilometers) of a lek. Dzialak et al (2012) documented sage-grouse during the winter avoiding haul roads associated with natural gas development. In contrast, Johnson et al (2011) found negative trends in counts of males on leks throughout the range of the species with increasing distance to interstate highway-although few leks occurred near interstates; relatively consistent slight negative trends in lek counts with distance to highways; and no relationship between distance to secondary roads and lek trends.…”
Section: Ro Adsmentioning
confidence: 99%